THE ORETICAL BASICS OF ENSURING FOOD SECURITY IN UZBEKISTAN (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article reveals the importance, essence and theoretical foundations of ensuring food safety. Based on the analysis of socio-economic changes and measures implemented to ensure food safety in Uzbekistan during the years of independence, it contains relevant proposals for strengthening the country's food safety.